Tinjauan Yuridis Terhadap Pasal 134 Ayat (4) Undang-Undang Nomor 1 Tahun 2015 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2014 Tentang Pemilihan Gubernur, Bupati Dan Walikota Menjadi Undang-Undang Pada Masa Daluwarsa Pelaporan Kasus Tindak Pidana Pemilihan Kepala Daerah Yang Relatif Singkat - Ulil Abshor; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Election of regional heads (Pilkada) is one way in the democratic system to elect regional heads in a particular region. The Regional Head Election aims to find qualified regional leaders in peaceful, honest and fair ways. Election of Regional Head is carried out by adopting the principle of direct, general, free, confidential, honest, and fair in accordance with Article 2 of Law Number 1 of 2015 concerning the Establishment of Government Regulations in lieu of Law Number 1 of 2014 concerning Election of Governors, Regents and Mayors to Become Constitution.This research is a type of normative juridical research or normative legal research. Normative juridical research or normative legal research is research that discusses legal principles, namely the legal principles contained in Act Number 1 of 2015 concerning Establishment of Government Regulations in lieu of Law Number 1 of 2014 concerning Election of Governors, Regents and the Mayor Becomes a Law.From the results of the research that the author did, it can be concluded that the reason for the expiration of regional head elections in terms of reporting is limited by the short time compared to criminal acts in general because there are several cases of reports that have not been completed, thus disrupting the process in the election for determine the winner in the election. If no deadline is set for reporting, it can be used as a loophole for one party to hinder the electoral process, and can also cause government vacancies as in previous cases. Second, the reporting deadline is in accordance with Article 134 paragraph (4) of Law Number 1 of 2015 concerning the Establishment of Government Regulations in lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayors into Laws which stipulate the reporting deadline of only 7 days are considered too fast and ineffective because many cases are killed because of these deadlines.Keywords : Juridical Review - Article 134 Paragraph (4) -Law number 1 of 2015